Mass spectrometry-based metabolomics for irritable bowel syndrome biomarkers. (November 2019) - Yu, Qihong; Liu, Xinru; Huang, Haojie; Zheng, Xingfeng; Pan, Xue; Fang, Junwei; Meng, Liyuan; Zhou, Chunhua; Zhang, Xiaocui; Li, Zhaoshen; Zou, Duowu
Background: Irritable bowel syndrome (IBS) is a common gastrointestinal disorder without obvious structural abnormalities or consistent associated biomarkers, making its diagnosis difficult. In the present study, we used a urine-based metabolomics approach to identify IBS biomarkers. Methods: We used an ultra-performance liquid chromatography/quadrupole time-of-flight mass spectrometry (UPLC-QTOF-MS) on urine samples from patients suffering from IBS and healthy controls. Data were coupled for multivariate statistical analysis methods. Results: We selected 30 differential metabolites associated with IBS and found steroid hormone biosynthesis and histidine metabolism alterations in patients with IBS that may be involved in the pathogenesis of the disease. In addition, we identified a panel of five metabolite markers composed of cortisone, citric acid, tiglylcarnitine, N6, -N6, -N6-trimethyl-L-lysine and L-histidine that could be used to discriminate between patients and healthy controls and may be appropriate as IBS diagnosis biomarkers. Conclusion: Our findings indicate that metabolomics combined with pattern recognition can be useful to identify disease diagnostic IBS markers. Clinical trial registration: ChiCTR1800020072